HUBUNGAN ANTARA KECEPATAN, VOLUME DAN KEPADATAN LALU LINTAS RUAS JALAN SILIWANGI SEMARANG - Nugroho Julianto, Eko (Semarang State University, 2010)
Abstract: The volume of traffic traveling on roads Siliwangi have increased from year to year. ThisisÃÂ dueÃÂ toÃÂ theÃÂ developmentÃÂ ofÃÂ thisÃÂ area. To overcomeÃÂ the problemÃÂ ofÃÂ trafficÃÂ congestion onÃÂ these roadsÃÂ isÃÂ requiredÃÂ priorÃÂ knowledgeÃÂ aboutÃÂ trafficÃÂ characteristicsÃÂ andÃÂ modelÃÂ ofÃÂ theÃÂ relationship between these characteristics. This study aims to analyze the model of the relationship between the characteristic volume (V), speed (S) and density (D)ÃÂ traffic, in accordance with existing conditions. Survey dataÃÂ includesÃÂ traffic volumes and speeds withÃÂ the manual count method, being analytical modelsÃÂ includeÃÂ modelsÃÂ Greenshield,ÃÂ Greenberg,ÃÂ andÃÂ Underwood.ÃÂ TheÃÂ resultsÃÂ showedÃÂ thatÃÂ the relationship model that is suitable for VSD Siliwangi road is to follow the model of Underwood with r = 0859, with the model of Us = 68.20 x exp(-D/-15.05). Keywords: relationship model, Greenshield, Greenberg, Underwood ÃÂ Abstrak: Volume perjalanan lalu lintas pada ruas jalan Siliwangi mengalami peningkatan dari tahun keÃÂ tahun.ÃÂ HalÃÂ iniÃÂ disebabkanÃÂ perkembanganÃÂ daerahÃÂ ini.ÃÂ UntukÃÂ mengatasiÃÂ masalahÃÂ kemacetan lalulintasÃÂ padaÃÂ ruasÃÂ jalanÃÂ iniÃÂ terlebihÃÂ dahuluÃÂ diperlukanÃÂ pengetahuan mengenaiÃÂ karakteristikÃÂ lalu lintasÃÂ dan modelÃÂ hubunganÃÂ antarÃÂ karakteristikÃÂ tersebut. KajianÃÂ iniÃÂ bertujuan menganalisis model hubunganÃÂ antarÃÂ karakteristikÃÂ volumeÃÂ (V),ÃÂ kecepatanÃÂ (S)ÃÂ danÃÂ kepadatanÃÂ (D)ÃÂ laluÃÂ lintas,ÃÂ sesuai dengan kondisi yang ada. Survai data meliputi volume dan kecepatanÃÂ laluÃÂ lintas dengan metode manualÃÂ count,ÃÂ sedangÃÂ analisis model meliputi modelÃÂ Greenshield,ÃÂ Greenberg,ÃÂ danÃÂ Underwood. Hasil analisis menunjukkan bahwa model hubungan V-S-D yang sesuai untuk ruasÃÂ jalan Siliwangi adalah mengikuti model Greenberg dengan nilaiÃÂ r = 0.773, dengan model Us = 68.20 x exp(-D/-15.05). Kata kunci: model hubungan, greenshield, greenberg, underwood